2016
DOI: 10.1007/s00408-016-9973-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal Anti-inflammatory Drugs may Worsen the Course of Community-Acquired Pneumonia: A Cohort Study

Abstract: Our findings suggest that NSAIDs, often taken by young and healthy patients, may worsen the course of CAP with delayed therapy and a higher rate of pleuropulmonary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 30 publications
1
46
0
1
Order By: Relevance
“…that NSAIDs were used to treat the earliest manifestations of a yet undiagnosed pneumonia) or detection bias suggested in previous studies. 10,11 In both analyses, follow-up continued until the earliest of outcome occurrence, end of study period (Sept 30 2015), crossover of exposure group or addition of comparator drug, medical or pharmacy disenrollment, death or 365 days post index date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…that NSAIDs were used to treat the earliest manifestations of a yet undiagnosed pneumonia) or detection bias suggested in previous studies. 10,11 In both analyses, follow-up continued until the earliest of outcome occurrence, end of study period (Sept 30 2015), crossover of exposure group or addition of comparator drug, medical or pharmacy disenrollment, death or 365 days post index date.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of pneumonia was strongest in the 5 days after exposure to oral NSAIDs, but weakened when these 5 days of follow up were removed from the analysis (main analysis)suggesting protopathic bias. [10][11][12] Prior research has found that individuals treated with NSAIDs in the days preceding admission to hospital for pneumonia had more severe presentations, possibly due to altered immune responses and longer times to antibiotic treatment. 11,12 Severe presentations increase the likelihood of pneumonia being diagnosed or detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NSAIDs intake was independently associated with the development of pleuroparenchymal complications (odds ratio = 2.57 [1.02-6.64], p = 0.049). Nevertheless, given the lack of consistent results about the direct effect of NSAIDs on the immunological response and the lack of controlled randomized studies in human, the authors could not conclude a direct effect of NSAIDs in the development of the complications of CAP [5]. Surely, in addition to the supposed interfering effect of NSAIDs with responses mediated by the prostaglandin and leukotriene pathways, NSAIDs, together with other antipyretic and analgesic medications, can be responsible for later presentation of symptoms or underestimation of the severity of the disease, both leading to a delayed diagnosis and possible worse prognosis.…”
mentioning
confidence: 99%